The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1002/j.1460-2075.1990.tb08317.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation by the papillomavirus E6 zinc finger oncoprotein.

Abstract: The introduction of the bovine (BPV) or human papillomavirus E6 gene into susceptible cells can result in their transformation, but there are few clues to the mechanism of action of the E6 gene. The characteristic features of E6 proteins are their small size (approximately 150 amino acids) and the potential to form two large zinc fingers. To determine if E6 can function as a transcription factor, the BPV E6 gene was fused to the sequence specific DNA binding peptide encoded by the BPV E2 gene. This chimeric E6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 45 publications
(37 reference statements)
3
21
0
Order By: Relevance
“…The results shown are the lacZ activity relative to that obtained with wild-type lexA-BE6 fusion. Because BE6-lexA fusions have endogenous transcriptional activation properties which are altered in BE6 mutants (Lamberti et al, 1990), OD405 values obtained in cultures expressing the empty B42-fusion vector alone were substracted from values obtained in the presence of B42-E6-AP or B42-paxillin fusions, to more closely approximate the lacZ activity resulting from the interaction of lexA-BE6 with E6-AP or paxillin. Transformation results re¯ect the induction of anchorage independent growth in nobel agar by BE6 mutants relative to wild-type BE6.…”
Section: Discussionmentioning
confidence: 99%
“…The results shown are the lacZ activity relative to that obtained with wild-type lexA-BE6 fusion. Because BE6-lexA fusions have endogenous transcriptional activation properties which are altered in BE6 mutants (Lamberti et al, 1990), OD405 values obtained in cultures expressing the empty B42-fusion vector alone were substracted from values obtained in the presence of B42-E6-AP or B42-paxillin fusions, to more closely approximate the lacZ activity resulting from the interaction of lexA-BE6 with E6-AP or paxillin. Transformation results re¯ect the induction of anchorage independent growth in nobel agar by BE6 mutants relative to wild-type BE6.…”
Section: Discussionmentioning
confidence: 99%
“…BPV-1 E6 stimulates transcription when targeted to a promoter (Lamberti et al, 1990), although cellular promoters responsive to BPV-1 E6 have not been identi®ed. Mutational analysis indicated that the transcriptional activation function of BPV-1 E6 is not su cient for cell transformation (Chen et al, 1997;Ned et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic binding affinity of HPV-16 E6 and E7 to the cellular tumour suppressors p53 and pRb, and the modulation of their expression by the LCR as well as by the P *( promoter, derepressed by the disruption of E2 during HPV integration into the cellular genome, have been correlated with their oncogenic properties in the pathogenesis of neoplasia of the female lower genital tract (Dyson et al, 1989 ;Werness et al, 1990 ;Scheffner et al, 1993Scheffner et al, , 1995Lambert & Howley, 1988 ;Lamberti et al, 1990 ;Schiller et al, 1989).…”
Section: Introductionmentioning
confidence: 99%